Achieving significantly enhanced dielectric performance of reduced graphene oxide/polymer composite by covalent modification of graphene oxide surface. (November 2015) - Tong, Wangshu; Zhang, Yihe; Zhang, Qian; Luan, Xinglong; Duan, Yang; Pan, Shaofeng; Lv, Fengzhu; An, Qi
Abstract: In this study, nanocomposite films of poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF–HFP) incorporating polyethylenimine (PEI)-covalently modified graphene sheets (rGO–PEI) were prepared by a solution-cast method, and the dielectric properties of the films were studied. Infrared spectroscopy, atom force microscope, X-ray photoelectron spectroscopy, solid state NMR spectroscopy, Raman, thermogravimetry analysis and additional verification experiment indicated that PEI chains were successfully grafted on the surface of graphene oxide (GO). A dielectric constant of 67 (100 Hz), which was five times that of pure PVDF–HFP film, was obtained for the composite films when the concentration of rGO–PEI was 8 wt% and the dielectric loss was as low as 0.12. A microcapacitor model explained the behavior of the dielectric composites. The effect of the covalent modification was further studied by introducing control experiments using non-covalently prepared N–GO–PEI as the fillers to create the composite films. The results demonstrated that covalent linkages between GO and PEI were indispensable in obtaining composite films with high dielectric constants and low losses.